Influenza vaccination responses: Evaluating impact of repeat vaccination among health care workers. Issue 19 (2nd May 2017) - Leung, Vivian K.Y.; Carolan, Louise A.; Worth, Leon J.; Harper, Susan A.; Peck, Heidi; Tilmanis, Danielle; Laurie, Karen L.; Slavin, Monica A.; Sullivan, Sheena G.
Abstract: Objective: To compare the antibody response to influenza between health care workers (HCWs) who have received multiple vaccinations (high vaccination group) and those who have received fewer vaccinations (low vaccination group). Design: Prospective serosurvey. Setting: Tertiary referral hospital. Participants: Healthcare workers. Methods: Healthcare workers were vaccinated with the 2015 southern hemisphere trivalent influenza vaccine. Influenza antibody titres were measured pre-vaccination, 21–28 days post-vaccination and 6 months post-vaccination. Antibody titres were measured using the haemagglutination inhibition assay. Levels of seropositivity and estimated geometric mean titres were calculated. Results: Of the 202 HCWs enrolled, 182 completed the study (143 high vaccination and 39 low vaccination). Both vaccination groups demonstrated increases in post-vaccination geometric mean titres, with greater gains in the low vaccination group. Seropositivity remained high in both high and low vaccination groups post-vaccination. The highest fold rise was observed among HCWs in the low vaccination group against the H3N2 component of the vaccine. Conclusions: Both high and low vaccination groups in our study demonstrated protective antibody titres post-vaccination. The findings from the current study are suggestive of decreased serological response among highly vaccinated HCWs. More studies with larger sample sizes and a greater number of people in the vaccine-naïve and once-vaccinated groups are required to confirm or refute these findings before making any policy changes.